2008
DOI: 10.1007/s10552-008-9144-7
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid intake and liver cancer: a case–control study in Greece

Abstract: In the context of a case-control study undertaken in Greece, we examined the role of six flavonoid classes in the etiology of hepatocellular carcinoma (HCC), by viral status, and of cholangiocarcinoma (CAC). Data and blood samples were collected between 1995 and 1998. Information about dietary intakes and covariates, including chronic infection with hepatitis B (HBV) and C (HCV) virus, were available for 250 HBV and/or HCV positive HCC cases, 83 HBV and HCV negative HCC cases, six CAC cases, and 360 hospital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
4
18
0
1
Order By: Relevance
“…Sharp et al reported a reduced risk of HCC in Japanese atomic bomb survivors with frequent soya food consumption (Sharp et al, 2005). The relation between some nutrients intake and HCC risk were investigated, among which favorable effect were reported including flavonoid (Lagiou et al, 2008), β-carotene (Polesel et al, 2007), retinoids (Yuan et al, 2006), selenium (Yu et al, 1991), etc.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Sharp et al reported a reduced risk of HCC in Japanese atomic bomb survivors with frequent soya food consumption (Sharp et al, 2005). The relation between some nutrients intake and HCC risk were investigated, among which favorable effect were reported including flavonoid (Lagiou et al, 2008), β-carotene (Polesel et al, 2007), retinoids (Yuan et al, 2006), selenium (Yu et al, 1991), etc.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…This favorable effect may be attributed to specific vitamins, micronutrients, or bioactive compounds contained in plant foods. Flavonoids, a large group of phytochemicals with a similar structure, naturally occurring in foods and beverages of plant origin, have been inversely related to the risk of various cancers of the digestive tract [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there is only one case-control study published from Greece evaluating the association between total flavonoid intake and HCC cancer risk, by hepatitis status. 19 The study showed that flavones and their main food sources (spinach and peppers) were significantly and inversely associated with HCC risk. However, in our cohort study, total flavonoids and flavanols (flavan-3-ol monomers and theaflavins), but not flavones, were inversely related to HCC.…”
Section: Discussionmentioning
confidence: 95%
“…In a Greek case-control study, flavone intake was inversely associated with HCC risk in both chronic hepatitis virus positive (highest versus lowest quintile, OR 5 0.50, 95% CI: 0.27-0.94; p trend 5 0.049) and negative cases (highest versus lowest quintile, OR 5 0.41, 95% CI: 0.16-1.06; p trend 5 0.084). 19 Furthermore, there is some evidence suggesting that fruits, the main food source of flavonoids in Western diets, 20 protect against HCC. 5 To our knowledge, there are no studies evaluating the association between NEAC and HCC risk.…”
mentioning
confidence: 99%